Handbook of industry 4.0 and SMART systems - Pascual, Diego Galar; Daponte, Pasquale, 1957-; Kumar, Uday (Professor of mechanical engineering) (CRC Press, 2020)
Industry 4.0 refers to fourth generation of industrial activity characterized by smart systems and internet-based solutions. This book describes the fourth revolution based on instrumented, interconnected and intelligent assets. The different book chapters provide a perspective on technologies and methodologies developed and deployed leading to this concept. With an aim to increase performance, productivity and flexibility, major application area of maintenance through smart system has been discussed in detail. Applicability of 4.0 in transportation, energy and infrastructure is explored, with effects on technology, organisation and operations from a systems perspective.
Keywords: Technological innovations.; Internet of things.; elektronické knihy; electronic books